2020
DOI: 10.1101/2020.02.25.964080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-dimensional synaptic organization of the human hippocampal CA1 field

Abstract: The hippocampal CA1 field integrates a wide variety of subcortical and cortical inputs, but its synaptic organization in humans is still unknown due to the difficulties involved studying the human brain via electron microscope techniques. However, we have shown that the 3D reconstruction method using Focused Ion Beam/Scanning Electron Microscopy (FIB/SEM) can be applied to study in detail the synaptic organization of the human brain obtained from autopsies, yielding excellent results. Using this technology, 24… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 56 publications
6
14
1
Order By: Relevance
“…Most synapses presented a simple, macular shape (around 87% for both AS and SS), in agreement with previous reports in different brain areas and species 44,45,46,38,30 . In our study, non-macular synapses constituted around 13% of the total synapses.…”
Section: Synaptic Shape Synaptic Size and Curvaturesupporting
confidence: 92%
See 4 more Smart Citations
“…Most synapses presented a simple, macular shape (around 87% for both AS and SS), in agreement with previous reports in different brain areas and species 44,45,46,38,30 . In our study, non-macular synapses constituted around 13% of the total synapses.…”
Section: Synaptic Shape Synaptic Size and Curvaturesupporting
confidence: 92%
“…In the present study, we found that the AS:SS ratio was 96.25:3.75. Preliminary results from our laboratory, using the FIB/SEM methodology, have shown that the AS:SS ratios are 98:2 and 96:4 in the stratum radiatum of the mouse and human CA1, respectively 29,30 . That is, the ratio of AS and SS in the CA1 field is similar in humans and rodents.…”
Section: Ratio Of As and Ssmentioning
confidence: 99%
See 3 more Smart Citations